Wea want apology! Tailoring service recovery and self-construal to earn customer forgiveness - Cheng, Eugene Xi Aw; Hui, Stephanie Wen Chuah; Sabri, Mohamad Fazli; Chong, Han Xi (Inderscience, 2022)
The purpose of this study is to examine the impacts of service recovery strategies and self-construal on customer forgiveness. A 2-service recovery (manipulated: apology vs. economic) × 2-self-construal (median: independent vs. interdependent) between-subject experiment was conducted with 164 subjects. Results showed: 1) when apology is given, customers with interdependent self-construal are more likely to forgive compared to customers with independent self-construal; 2) forgiveness negatively influences negative-word-of-mouth. This study provides insight to the literature by indicating that service recovery strategies need to be compatible with customers' self-construal in order to earn forgiveness following a service failure.